F.R. David - "Inverted commas" - Holder, Will; Wijnen, Riet (Glasgow : ub books, 2017)
van Beek, Willem ; Bergs, Steyn ; Eshun, Kodwo ; Hartman, Rudo ; van der Heide, Yolande ; De Keukeleire-Van Snick, Marijke ; Kopsa, Maxine ; Kuipers, Maritt Serena ; van Loon, Erica ; Marroquin, Raul ; Oldham, Christian ; Schuster, Aaron ; Sirkel, Indrek ; Timonen, Maija ; Wikström, Josefine ; Vishmidt, Marina ; Waterman, Alex ; Williams, Luke
Didion, Joan ; Farocki, Harun ; Tolmie, Cara ; Nijhoff, A.H. ; Guest, Barbara ; Lütticken, Sven ; Tripp, Sarah ; van Snick, Philippe ; Oliveros, Pauline ; Lippard, Lucy ; Holder, Will ; Metzinger, Thomas ; Baracka, Amiri ; Brouwn, Stanley ; Doubiago, Sharon ; Weiner, Hannah ; Griffiths, Paul ; Federici, Silvia
Each issue of ‘F.R. David’ features a wide array of artists and writers and a unique theme.
boek